School and Teacher Factors That Promote Adolescents’ Bystander Responses to Social Exclusion - Mulvey, Kelly Lynn; Gönültaş, Seçil; Irdam, Greysi; Carlson, Ryan G.; DiStefano, Christine; Irvin, Matthew J. (Frontiers in Psychology, 2021)
Schools may be one important context where adolescents learn and shape the behaviors necessary for promoting global inclusivity in adulthood. Given the importance of bystanders in halting bullying and peer aggression, the focus of this study is on both moral judgments regarding one type of bullying, social exclusion, and factors that are associated with bystander intervention. The study includes 896 adolescents, who were 6th (N = 450, Mage = 11.73), and 9th (N = 446, Mage = 14.82) graders, approximately evenly divided by gender. Participants were primarily European–American (63.3%). Results revealed that girls and participants who perceived better relationships between students and teachers were more likely to judge exclusion to be wrong. Further, ethnic minority participants, those who were more anxious about being rejected by their teachers and reported more teacher discrimination were less likely to judge exclusion as wrong. Participants who reported more positive student–teacher relationships, perceptions of a more positive school social environment and more prior experiences of teacher discrimination were more likely to report that they would seek help for the victim. On the other hand, participants who reported being more angry about teacher rejection, experiencing either peer or teacher discrimination, and perceiving they are excluded from opportunities at school were less likely to intervene to come to the aid of a peer who is being excluded. The results document the complex interplay of school and teacher factors in shaping adolescents’ bystander responses to social exclusion. Our findings suggest that positive school climate can promote intentions to intervene. However, findings indicate that adolescents who are marginalized in their school environments, and who report experiences of rejection, exclusion or discrimination are not willing or likely to intervene to prevent others from experiencing exclusion.